Empirical and behavioural economic applications to the energy sector - Klege, Rebecca Afua (University of Cape Town, 2020)
This thesis contributes to the energy literature by leveraging insights from empirical and experimental economics. The thesis presents four papers with a common goal of understanding specific themes in the energy sector namely: households energy use patterns, behavioural preferences among entrepreneurs operating energy businesses and applications of behavioural nudges to reduce energy use. The first paper set the tone for the two subsequent chapters. The paper: 'Energy Choices and Tenancy in Rwanda' examines the energy choice patterns of households based on their rental status and dwelling types. The fifth Integrated Household Living Conditions Survey (EICV5) conducted over one year, October 2016 to October 2017, together with a bivariate probit model is used. A heterogeneous analysis focused on gender and income differentiated impacts, as well as geographical differences based on the tenancy status of households, is further examined. The results signal that households energy choices in Rwanda differ by rental and dwelling types. The second and third papers ascertain the role of competition and risk preferences among entrepreneurs working in off-grid renewable energy microenterprises and its effects on business success in the context of including more women as entrepreneurs in the energy sector. Specifically, the second paper: 'Competition and Gender in the Lab vs Field: Experiments with Off-Grid Renewable Energy Entrepreneurs in Rural Rwanda' examines the gender differences in competitiveness and how this affects the business success of entrepreneurs operating renewable energy enterprises. Results from the economic experiments are compared to the day to day activities of the business. Findings show that female entrepreneurs are not less likely to compete and are not outperformed by male entrepreneurs. This stands in contrast to several studies, mostly conducted on university students of developed countries. The third paper: 'Risk attitudes, Gender and Business Performance Among off-grid Renewable Energy Entrepreneurs in Rural Rwanda' in a similar context examines the risk attitudes among entrepreneurs and its effect on the performance from a gender perspective. The study adopts a choice list experimental approach to elicit risk attitudes. The results indicate a strong risk aversion among entrepreneurs. The risk aversion found is higher for women compared to men. Entrepreneurs with high risk-taking abilities also tend to record better performance levels. The paper concludes that policies geared towards hedging against risk aversion in entrepreneurial programs may be vital in reducing gender gaps in business performance. The fourth paper: 'The power of nudging: Using feedback, competition and responsibility assignment to save electricity in a non-residential setting' answers the question 'can behavioural interventions achieve energy savings in non-residential settings where users do not face the financial consequences of their behaviour?' The paper relies on a randomized control trial and two behavioural interventions. Results show that behavioural nudges can be useful in reducing energy consumption in a non-residential environment.